Quality of life among patients with lower limb osteoarthritis in Hospital Universiti Sains Malaysia - Nazeri, Nuranis Milani Ahmad (Universiti Sains Malaysia, 2023)
Quality of life is an important component in patient’s well-being, which considered as a goal of treatment in chronic illness. A cross-sectional study was carried out to identify the quality of life among the patients with lower limb osteoarthritis in Hospital USM. The questionnaire used in this study was Osteoarthritis Knee and Hip Quality of Life (OAKHQOL) which adapted from Kadir et al. (2018). A total of 100 patients in Hospital USM who fulfilled the inclusion and exclusion criteria were approached to participate in this study. Data collected were statistically analysed using the SPSS software version 26.0. Pearson’s Chi Square were used for data analysis for the association between sociodemographic characteristics and quality of life. For physical activity, the average mean was 40.45 (SD 23.03), mental health 22.33 (SD 19.77), pain 25.46 (SD 11.07), social functioning 26.78 (SD 3.21) and social support 27.56 (SD 2.16). There is a significant association between age and types of osteoarthritis with physical activity (p = 0.030), level of education with mental health (p = 0.01), age and Body Mass Index with pain (p = 0.001). Lastly, there is no significant association between the sociodemographic characteristics with social support and social functioning. In conclusion, the findings of this study showed that the quality of life among patients with lower limb osteoarthritis was the worst in pain domain and the best in social functioning.